JunB and Bcl-2 overexpression results in protection against cell death of nigral neurons following axotomy - Winter, Christine; Weiss, Christoph; Martín-Villalba, Ana; Zimmermann, Manfred; Schenkel, Johannes (Brain research. Molecular brain research, 2002)
Transection of the medial forebrain bundle is a well established approach to investigate neuronal cell body response in the derived neuronal populations of the substantia nigra pars compacta (SNC). This model of central axotomy leads in mouse within 50 days post transection to degeneration of up to 70% of the affected SNC neurons. A central component of the axotomy induced alterations leading to neuronal degeneration is the rapid induction, lasting expression and activation of the c-Jun transcription factor. However, the role of c-Jun in the process of neuronal degeneration is not fully understood. Since null mutations of c-Jun cause embryonic lethality, this study was designed to investigate the impact of two c-Jun modulating proteins on neuronal survival after axotomy in transgenic mice: JunB, a Jun family member affecting c-Jun expression, and Bcl-2, an antiapoptotic protooncogene interacting among others with the c-Jun N-terminal kinases. In JunB as well as in Bcl-2 transgenic mice the long term survival rate of transected SNC neurons was remarkably increased when compared to wildtype controls. These effects were obviously achieved by cellular modulations directly following axotomy: Whereas JunB overexpression attenuated c-Jun induction and simultaneously led to a higher phosphorylation rate of c-Jun in SNC neurons, Bcl-2 overexpression did not influence c-Jun expression, but resulted in a reduced phosphorylation state of c-Jun in transected SNC neurons. We therefore conclude that the early phosphorylation rate of c-Jun might play an important role for the long term fate of transected neurons.